COLLABORATIVE GOVERNANCE DALAM PEMBERDAYAAN MASYARAKAT DISABILITAS DI DESA MARON KECAMATAN GARUNG KABUPATEN WONOSOBO - Winarni, Liliek; Afni, Ika Nur; Wirawan, Riska (Badan Riset dan Inovasi Daerah Provinsi Jawa Tengah, 2021)
People with disabilities are citizens who must get equal rights, but they are often marginalized and live less properly. Disability issues are not only the responsibility of the central government, but other stakeholders are also responsible. The purpose of this study is to find out how far the role played by stakeholders in solving existing problems. This study aims to determine the collaborative governance carried out by the Maron Village government with the Wonosobo District Social Service, the Temanggung District Social Service, Tali Kasih KSM and the private sector, namely the local community in empowering people with disabilities. Methods This research uses a qualitative approach. Data collection techniques were carried out through interviews with stakeholders involved in empowering people with disabilities and documents as secondary data. The results of the study show that collaborative governance in empowering people with disabilities has not gone well. This can be seen from the indicators of collaborative governance according to DeSeve that have not been achieved, namely the absence of a strong commitment to all stakeholders, the absence of strong trust between stakeholders, the absence of official rules related to collaboration for empowering people with disabilities and not having access to resources that are still limited, especially the budget. and infrastructure. The recommendation in this study is that the government can create a national assistance program for disability, the government cooperates with MSMEs for disability empowerment.